ANALISIS UNGKAPAN TRADISIONAL DALAM RITUAL VAU DI DESA TAYANDO YAMTEL KECAMATAN TAYANDO TAM (KAJIAN ETNOLINGUISTIK) - Ahmat Renhoat; Susi Hardila Latocinsina; Nanik Handayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to identify and describe the forms and meanings of symbols embedded in the traditional expressions of the Vau ritual from an ethnolinguistic perspective. A descriptive qualitative method was employed in this study. The research data consist of traditional expressions, which were collected through interviews, observation, and documentation techniques. The results demonstrate that these traditional expressions are structured across several main stages: Wasar (the proposal), Hurak (determining the wedding day), Iyak sit yahau lilan (the exchange of rings), as well as the stages of handing over heirloom dowries (Lela, Mariyam, Gong) and the logistics distribution rite (bawiyar ai). Semiotically, the use of metaphors such as